2021
DOI: 10.1007/s00167-021-06803-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with successful 5-year outcomes following arthroscopic Bankart repair in athletes

Abstract: Purpose The purpose of this study was to evaluate the outcomes of athletes 5-years post-operatively following arthroscopic Bankart repair, and to evaluate factors associated with satisfaction and shoulder function, as deined by subjective shoulder value. Methods A retrospective review of athletes who underwent arthroscopic Bankart repair, with a minimum of 5-year follow-up was performed. Recurrence, Visual Analogue Scale (VAS) score, Subjective Shoulder Value (SSV), satisfaction, and whether they would undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Arthroscopic Bankart repair (ABR) using suture anchors is a common surgical treatment for recurrent anterior shoulder instability. Many surgeons have performed ABR in which the labrum, including the anteroinferior glenohumeral ligament (AIGHL), is repaired at the articular edge for patients with small or no bone defects [1][2][3], and it has been found to improve pain and functional outcomes in the majority of patients [4,5]. However, some authors reported that approximately one-third of athletes did not return to their preinjury level of sports performance [6], and Miura et al demonstrated that ABR still resulted in a signiicantly high rate of recurrent instability, such as subluxation or apprehension [7].…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic Bankart repair (ABR) using suture anchors is a common surgical treatment for recurrent anterior shoulder instability. Many surgeons have performed ABR in which the labrum, including the anteroinferior glenohumeral ligament (AIGHL), is repaired at the articular edge for patients with small or no bone defects [1][2][3], and it has been found to improve pain and functional outcomes in the majority of patients [4,5]. However, some authors reported that approximately one-third of athletes did not return to their preinjury level of sports performance [6], and Miura et al demonstrated that ABR still resulted in a signiicantly high rate of recurrent instability, such as subluxation or apprehension [7].…”
Section: Introductionmentioning
confidence: 99%
“…RTP is often an athlete's primary concern with anterior shoulder instability. Indeed, Hurley et al 39 found that the biggest predictor of satisfaction at 5-year post-surgical intervention was the ability to RTP. Overall, we found high rates of return to sports irrespective of surgical technique ranging from 70% to 86% with mean times of RTP of 5 to 7 months.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 2021, Hurley et al followed 144 patients for a 5-year follow-up and showed 82.6% of patients were satisfied/very satisfied with Bankart Repair. 9 However, these studies are limited by smaller cohort sizes. Comparatively, our study demonstrated that 52% of Instagram posts had a positive tone.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 2017, Ramkumar et al analyzed 3,145 posts related to ACL reconstruction, which were made by patients, surgeons, and hospitals. 9 The most common types of content were personal recovery stories (92% of overall posts), with an emphasis on wound appearance, the rehabilitation process, and return to play. 11 These results differ from our study, as only 2.5% of patients posted about their wound appearance.…”
Section: Discussionmentioning
confidence: 99%